Harmony at Sea: A Study of Fishermen's Community Solidarity in Lala Village, Buru Regency - Radi Udin Alfian Sangaji; M. Rusdi M. Rusdi; Adriani Galry Adoniram Tobondo; Ismail Ismail; Randi Randi (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
In the fishing community, social solidarity is a fundamental aspect of daily life, fostering deep social interactions among members. This qualitative and descriptive study examines the manifestations of social solidarity within the fishermen's activities. Data collection techniques include observation, interviews, and documentation, with research informants selected through purposive sampling. Analysis involves data reduction, presentation, and verification. The findings reveal two forms of solidarity: (1) Cooperative solidarity, evident during fishing trips, and (2) collaborative solidarity, observed during activities such as boat repairs, net mending, coastal area cleaning, and providing assistance at sea. This research sheds light on the importance of social solidarity in enhancing the efficiency and well-being of the fishing community. In addition to highlighting the diverse forms of solidarity within the fishing community, this research offers valuable insights for policymakers, community leaders, and fisheries management. Understanding the dynamics of social solidarity among fishermen can lead to more effective support and resource allocation.